(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Pre-eclampsia is a major cause of mortality and morbidity during pregnancy and childbirth. There are recommendations on use of medications to prevent preeclampsia, including low dose aspirin. Objective: The objective of this review is to discuss role of aspirin in reducing the incidence and maternal mortality and morbidity due to preeclampsia including its dose and duration of use. Methods: Review of available literature in internet and from libraries. Results: Four large randomized trials have demonstrated a reduction in the incidence of preeclampsia in patients treated with low-dose aspirin prophylaxis compared with placebo/ no treatment (15 versus 19 percent, 18 versus 20 percent, 6.7 versus 7.6 percent, and 1.6 versus 4.3 percent); however, the results were statistically significant in only the last trial. When data from these and other trials were pooled, meta-analyses supported the significance of the trend observed in individual trials. When begun early in the second trimester, use of low-dose aspirin (75-150 mg) reduced the incidence of preeclampsia by at least 10 percent, with the greatest absolute benefit in women at moderate to high risk of developing the disease. Serious sequelae of early onset preeclampsia, such as preterm birth and fetal growth restriction, were also reduced. Conclusion: Low-dose aspirin reduces the frequency of preeclampsia, as well as related adverse pregnancy outcomes (preterm birth, growth restriction), by about 10 to 20 percent when given to women at moderate to high risk of the disease. It has an excellent maternal/ fetal safety profile in pregnancy. WHO recommends Low-dose acetylsalicylic acid (aspirin, 75 mg) for the prevention of preeclampsia in women at high risk of developing the condition; should be initiated before 20 weeks of pregnancy. It should be taken preferably from 13th week of pregnancy, daily, regularly and may be discontinued 5 to 10 days before delivery. Bangladesh J Obstet Gynaecol, 2017; Vol. 32(2) : 106-116